Use of polymer combinations in the preparation of solid dispersions of a thermally unstable drug by hot-melt extrusion - Jia Liu; Feng Cao; Can Zhang; Qineng Ping (Elsevier, 2013)
The objective of the study was to prepare solid dispersions containing a thermally unstable drug by hot-melt extrusion (HME). Carbamazepine (CBZ) was selected as model drug and combinations of Kollidon VA64 (VA64), Soluplus (SOL) and Eudragit EPO (EPO) were utilized as carriers. Preformulation was conducted to identify the suitability of polymer combinations based on solubility parameters, differential scanning calorimetry (DSC), hot stage microscopy and thermogravimetric analysis. Physicochemical properties of solid dispersions were determined by DSC, X-ray diffraction, fourier transform infrared spectroscopy, dissolution and accelerated stability testing. The results show that drug-polymer miscibility at temperatures below the melting point (Tm) of CBZ was improved by combining EPO with VA64 or SOL. With 30% drug loading in a solid dispersion in SOL:EPO (1:1, w/w), CBZ was mainly present in an amorphous form accompanied by a small amount of a microcrystalline form. The dissolution rate of the solid dispersion was significantly increased (approximately 90% within 5 min) compared to either the pure drug (approximately 85% within 60 min) or the corresponding physical mixture (approximately 80% within 60 min) before and after storage. The solid dispersion in SOL:EPO (1:1, w/w) was relatively stable at 40 °C/75% RH under CBZ tablet packaging conditions for at least 3 months. In conclusion, polymer combinations that improve drug-polymer miscibility at an HME processing temperature below the Tm of a drug appear to be beneficial in the preparation of solid dispersions containing thermally unstable drugs.